Can Workers Still Climb the Social Ladder as Middling Jobs Become Scarce? Evidence from Two British Cohorts - Cecilia Garcia-Pe\~nalosa; Fabien Petit; Tanguy van Ypersele (Center for Economic Studies and ifo Institute (CESifo), 2023)
The increase in employment polarization observed in several high-income economies has coincided with a reduction in inter-generational mobility. This paper argues that the disappearance of middling jobs can drive changes in mobility, notably by removing a stepping stone towards high-paying occupations for those from less well-off family backgrounds. Using data from two British cohorts who entered the labour market at two points in time with very different degrees of employment polarization, we examine how parental income affects both entry occupations and occupational upgrading over careers. We find that transitions across occupations are key to mobility and that the impact of parental income has grown over time. At regional level, using a shift-share IV-strategy, we show that the impact of parental income has increased the most in regions experiencing the greatest increase in polarisation. This indicates that the disappearance of middling jobs played a role in the observed decline in mobility.
Keywords: J21; J24; J62; O33; R23; 330; British cohort; inter-generational mobility; job polarization; parental income; occupational transition